Relationship Between Temperature, Rainfall, Humidity and Wind Speed to the Occurrence of ARI in Kisaran Timur District - Hasani, Ade Putri Pertiwi; Harahap, Reni Agustina (Jurnal Kesmas Prima Indonesia, 2025)
ISPA is a significant global health problem. The purpose of this study was to determine the relationship between temperature, rainfall, humidity and wind speed with the incidence of ISPA in East Kisaran City in 2024. This study is a quantitative study, with a case control approach. This study was conducted in the working area of ​​the East Kisaran City Health Center. This study was conducted from August 2024 to January 2025. The population in this study was 175 people in East Kisaran City. The research sample was 60 consisting of 30 case samples and 30 control samples. Data collection using questionnaires, observations and direct interviews. The analysis used univariate analysis, in the form of descriptive, bivariate analysis using the chi square test via SPSS software. This study found a significant relationship between temperature and the incidence of ARI in the Kisaran Timur District, (p = 0.00, OR = 13.143), wind speed with the incidence of ARI in the Kisaran Timur District, (p = 0.000,), rainfall with the incidence of ARI in the Kisaran Timur District, (p = 0.016), humidity with the incidence of ARI in the Kisaran Timur District, (p = 0.000, OR = 16.249). In conclusion, in general, weather factors have a significant influence on the incidence of ARI. However, this influence is complex and influenced by various other factors. To prevent ARI, it is important to maintain environmental cleanliness, maintain immunity, and avoid exposure to risk factors such as air pollution.